Traumatic brain injury and co-occurring problems in prison populations: A systematic review. (6th June 2016) - O'Rourke, Conall; Linden, Mark A.; Lohan, Maria; Bates-Gaston, Jackie
Abstract: Background : A growing body of epidemiological research suggests high rates of traumatic brain injury (TBI) in prisoners. The aim of this review is to systematically explore the literature surrounding the rates of TBI and their co-occurrences in a prison population. Methods : Six electronic databases were systematically searched for articles published between 1980–2014. Studies were screened for inclusion based on pre-determined criteria by two researchers who independently performed data extraction. Study quality was appraised based on a modified quality assessment tool. Results : Twenty-six studies were included in this review. Quality assessment ranged from 20% (poor) to 80% (good), with an overall average of 60%. Twenty-four papers included TBI prevalence rates, which ranged from 5.69–88%. Seventeen studies explored co-occurring factors including rates of aggression ( n = 7), substance abuse ( n = 9), anxiety and depression ( n = 5), neurocognitive deficits ( n = 4) and psychiatric conditions ( n = 3). Conclusions : The high degree of variation in TBI rates may be attributed to the inconsistent way in which TBI was measured, with only seven studies using valid and reliable screening tools. Additionally, gaps in the literature surrounding personality outcomes in prisoners with TBI, female prisoners with TBI and qualitative outcomes were found.